Disparities in pension financing in Europe: economic and financial consequences - Chateau, Jean; Chojnicki, Xavier (Paris, 2006)
"We present a quantitative analysis of the impact of differential ageing and pension reforms on capital and labour market and, in particular, on intra-European capital flows. To this end, we develop a stylized general equilibrium model with overlapping generations of heterogeneous agents for the three largest European countries: France, Germany and the United-Kingdom. The model presents a structure halfway between pure general equilibrium models with rigorous microeconomic foundations accounting models where the macroeconomic environment remains exogenous. We show that the dynamics of capital accumulation and pension system sustainability are totally different depending on the assumption concerning economic openness. Two main conclusions may be drawn from the examination of the various prospective scenarios. First of all, the critical assumptions for PAYG systems are the future trend of the global factor productivity and the behavior of agents concerning activity and labour market participation. Secondly, in the long run, resorting to debt financing seems to be a dead end to finance retirement systems."